Assessment of sociodemographic factors and socio-economic status affecting the coverage of compulsory and private immunization services in Istanbul, Turkey - TOPUZOĞLU, AHMET; ÖZAYDIN, AYŞE NİLÜFER; SAVE, DİLŞAD (W B SAUNDERS CO LTD, 2005)
Objectives: The primary objective of this study was to determine the coverage of the Expanded Programme of Immunization (EPI) of the Ministry of Health and the coverage of private vaccines in the Umraniye Health District in order to establish approaches for improving vaccination services. Other objectives were to define the areas that present higher risks for non-vaccination and to determine the factors that influence vaccination coverage. Methods: A '30X7' cluster sampling design was adopted as the sampling method. Thirty streets were selected at random from each healthcare region. Sociodemographic and socio-economic characteristics of the population, utilization of vaccination services and vaccination status of children under the age of 5 years were determined by face-to-face interviews. Odds ratios for the sociodemographic and socio-economic characteristics, health centre region and inner country immigration were assessed as possible related factors with the vaccination coverage rates for children under 5 years and under 1 year using the backward elimination method in logistic regression. Results: Vaccination coverage was as follows: hepatitis B third dose, 84.6%; Bacitle Calmette-Guerin, 94.8%; diphtheria, tetanus, pertussis (DPT) third dose, 90.1%; oral polio virus (OPV) third dose, 90.0%; measles, 88.7%; DPT booster dose, 79.1%; OPV booster dose, 79.0%; measles, mumps, rubella (MMR), 13.3%; haemophilus influenza type b (Hib), 9.3%; and Varicella vaccine, 3.3%. The full vaccination rates for children under 5 years and under 1 year were 68.3 and 79.5%, respectively. Higher socioeconomic status was associated with a higher rate of full vaccination and private vaccination for children under 5 years of age. Conclusions: Full vaccination rates for children aged less than 1 year and less than 5 years were higher in our district than in Istanbul. However, we did not meet the EPI aims for any of the vaccines, and differences were observed in vaccination coverage rates between different socio-economic groups in the district. Therefore, an intervention programme should be considered to achieve the EPI's goals, particularly in socio-economically disadvantaged groups. Also, the coverage of private vaccination (MMR, Hib, Varicella) is tow and more children from higher socioeconomic groups receive these vaccines. (c) 2005 The Royal Institute of Public Health. Published by Elsevier Ltd. ALL rights reserved.
Keywords: socio-economic; sociodemographic; coverage; vaccination; vaccine; EPI; Turkey; VACCINATION; MEASLES